2016
DOI: 10.1027/0227-5910/a000378
|View full text |Cite|
|
Sign up to set email alerts
|

Bullying, Depression, and Suicide Risk in a Pediatric Primary Care Sample

Abstract: The study's limitations include the use of cross-sectional and self-data reports. When medical providers evaluate suicide risk, bullying should be considered as a possible precipitant, especially if the patient is depressed. Verbal bullying may be particularly important in understanding severity of suicide risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 20 publications
(18 reference statements)
7
51
0
4
Order By: Relevance
“…The findings of Elgar et al [44] and Kodish et al [46] suggested that the health consequences of cybervictimisation are not completely attributable to its co-occurrence with face-to-face bullying. Similarly, the correlations reported in Fu et al [26] between cybervictimisation and unnatural child deaths were independent of traditional bullying.…”
Section: Cyberbullying Involvementmentioning
confidence: 93%
See 4 more Smart Citations
“…The findings of Elgar et al [44] and Kodish et al [46] suggested that the health consequences of cybervictimisation are not completely attributable to its co-occurrence with face-to-face bullying. Similarly, the correlations reported in Fu et al [26] between cybervictimisation and unnatural child deaths were independent of traditional bullying.…”
Section: Cyberbullying Involvementmentioning
confidence: 93%
“…Eleven were of high quality, 16 medium, and three low. Regression coefficients ranged from β = 0·15 (P < ·01) for suicide risk [46] to β = 0·97 (P < ·001) for suicidal behaviour [47]. goodness-of-fit producing χ 2 (2, 138) = 9·09 (P = ·03) when the frequencies of suicidal planning and attempts between cybervictims and controls were compared.…”
Section: Cybervictimisation and Suicidal Behavioursmentioning
confidence: 99%
See 3 more Smart Citations